Physiotherapy in the surgical treatment of Chagasic Megaesophagus - Vento, Daniella Alves; Araújo, Isabella Ribeiro; de Souza Filho, Luiz Fernando Martins; Oliveira, Michael Taylor (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2019)
Introduction:Chagasic Megaesophagus (CME) is the manifestation of the disease characterized by luminal enlargement and muscular hypertrophy. Physiotherapy is an area that can be beneficial to CME patients in both pre and postoperative stages due to evidence of its success rate in preventing pulmonary complications. Objective:analyze the use of physiotherapeutic treatment in treating patients that underwent surgical treatment for CME. Methods: Study developed at University Federal of Goiás- Hospital das Clínicas, in Goiânia – Goiás. Of the 1096 surgical procedures, 38 of them were to treat CME. Results: was an average age of 59,4±13 years, 77% male and 23% female, physiotherapeutic care was part of the postoperative routine in 68% of the cases with no record of its occurrence in the preoperative stages.Conclusion: Physiotherapy was used only in the postoperative stage. Despite the importance of Physiotherapy in the treatment of CME, the studies pertaining to its use in this context are scarce. As a result, more research is necessary to emphasize that its use from the moment of hospitalization could increase the possibilities of surgical recovery.